The Rhetoric of KH Jujun Junaedi in Developing Sufi Preaching at Pesantren Al-Jauhari - Witrin Noorjutstiatini; Dadang Muliawan; Muhamad Rijaldi; Yufi Mohammad Nasrullah; Fiqra Muhamad Nazib (al-Afkar, Journal For Islamic Studies, 2025)
This research explores the role of KH Jujun Junaedi's rhetoric in the development of Sufism (Tasawuf) preaching at Pesantren Al-Jauhari. The study examines how KH Jujun Junaedi uses rhetorical techniques to deliver Sufism teachings effectively and persuasively, aiming to establish a deep connection with his audience. The research employs a qualitative approach, using phenomenology and rhetorical analysis to understand how the rhetoric affects the understanding and practice of Sufism among the santri and community at the pesantren. The findings indicate that his rhetorical approach, blending educational, recreational, and informative elements, is crucial in making the teachings accessible and impactful. The study also identifies supporting and hindering factors in the implementation of his rhetoric, such as his popularity, communication style, and physical challenges related to aging. This research contributes to the understanding of the intersection between rhetoric and religious teaching, particularly in the context of Sufism at Islamic boarding schools.